Training and Coaching as a Solution to Improve Nazhir's Professionality in Jekan Raya District, Palangka Raya City - Maula, Bani Syarif; Akbar, Wahyu; Sayuti, M. Noor; Zulkifli; Permana, Farid; Novia; Rafi, Faris; Putra, Faiq Danendra Rizqi; Rahima, Dwira (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2022)
Nazhir's professionality in Jekan Raya District is not optimal, because there are still some who do not carry out their duties after becoming Nazhir, one of which is not reporting the implementation of waqf assets to the Indonesian Waqf Board (BWI), did not receive any prior guidance or training related to the management and development of waqf, and that is one of BWI's duties regarding its duties and authorities which has not been implemented until now. This community service activity carried out by the Zakat and Waqf management study program FEBI IAIN Palangka Raya, aims to strengthen Nazhir's competence and professionalism through reporting assistance carried out with outreach activities and FGD in Jekan Raya sub-district.t. 100% of participants attended the activity and followed until the activity was finished. The results showed that participants gained new knowledge about the development of waqf management and realized the importance of waqf reporting, this became an increase in knowledge professionalism and competence for nazhir. Participants are interested in trying to practice it in the implementation of waqf management. It is hoped that this activity can increase waqf, especially in the Jekan Raya sub-district, Palangka Raya City.